2022
DOI: 10.3390/biom12121877
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Pathways Stratify Colorectal Cancer into Two Subtypes with Distinct Cartilage Oligomeric Matrix Protein (COMP) Expression-Related Characteristics

Abstract: Background: Colorectal cancers (CRCs) continue to be the leading cause of cancer-related deaths worldwide. The exact landscape of the molecular features of TGF-β pathway-inducing CRCs remains uncharacterized. Methods: Unsupervised hierarchical clustering was performed to stratify samples into two clusters based on the differences in TGF-β pathways. Weighted gene co-expression network analysis was applied to identify the key gene modules mediating the different characteristics between two subtypes. An algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Several clinical studies have suggested that inflammatory tissue conditions promote cancer development; in particular, some evidence pointed out a relationship between the activation of inflammatory cytokines and a poor prognosis in patients with CRC [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical studies have suggested that inflammatory tissue conditions promote cancer development; in particular, some evidence pointed out a relationship between the activation of inflammatory cytokines and a poor prognosis in patients with CRC [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Impaired regulation of serum levels of proinflammatory cytokines, such as Transforming Growth Factor β (TGF-β) and Tumor Necrosis Factor Alpha (TNF-α), and the down-expression of Peroxisome Proliferator Activated Receptor Gamma (PPAR-γ), known to be a growth-limiting and differentiation-promoting factor, are major signaling pathways involved in the pathogenesis of CRC [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%